Measurement of cerebral ABCC1 transport activity in wild-type and APP/PS1-21 mice with positron emission tomography. Issue 5 (May 2020) - Zoufal, Viktoria; Mairinger, Severin; Krohn, Markus; Wanek, Thomas; Filip, Thomas; Sauberer, Michael; Stanek, Johann; Kuntner, Claudia; Pahnke, Jens; Langer, Oliver
Previous data suggest a possible link between multidrug resistance-associated protein 1 (ABCC1) and brain clearance of beta-amyloid (Aβ). We used PET with 6-bromo-7-[ 11 C]methylpurine ([ 11 C]BMP) to measure cerebral ABCC1 transport activity in a beta-amyloidosis mouse model (APP/PS1-21) and in wild-type mice aged 50 and 170 days, without and with pretreatment with the ABCC1 inhibitor MK571. One hundred seventy days-old-animals additionally underwent [ 11 C]PiB PET scans to measure Aβ load. While baseline [ 11 C]BMP PET scans detected no differences in the elimination slope of radioactivity washout from the brain (kelim ) between APP/PS1-21 and wild-type mice of both age groups, PET scans after MK571 pretreatment revealed significantly higher kelim values in APP/PS1-21 mice than in wild-type mice aged 170 days, suggesting increased ABCC1 activity. The observed increase in kelim occurred across all investigated brain regions and was independent of the presence of Aβ plaques measured with [ 11 C]PiB. Western blot analysis revealed a trend towards increased whole brain ABCC1 levels in 170 days-old-APP/PS1-21 mice versus wild-type mice and a significant positive correlation between ABCC1 levels and kelim . Our data point to an upregulation of ABCC1 in APP/PS1-21 mice, which may be related to an induction of ABCC1 in astrocytes as a protective mechanism against oxidative stress.